2016
DOI: 10.1007/s10544-016-0128-1
|View full text |Cite
|
Sign up to set email alerts
|

Human pancreatic stellate cells modulate 3D collagen alignment to promote the migration of pancreatic ductal adenocarcinoma cells

Abstract: A hallmark of pancreatic ductal adenocarcinoma (PDAC) is the ability for cancer cells to aggressively infiltrate and navigate through a dense stroma during the metastatic process. Key features of the PDAC stroma include an abundant population of activated pancreatic stellate cells (PSCs) and highly aligned collagen fibers; however, important questions remain regarding how collagen becomes aligned and what the biological manifestations are. To better understand how PSCs, aligned collagen, and PDAC cells might c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 108 publications
1
27
0
Order By: Relevance
“…An additional explanation is that within αSMA + myofibroblast are present subsets of cells with different functional behaviors, with either positive or negative effects on tumor cell growth. After depletion of all αSMA + myofibroblast, these populations are lost and PDAC can grow without any brake ( 168 , 173 , 175 , 177 , 183 ). In such TME, immune system can receive misleading information with conflicting, undesired outcomes.…”
Section: Can Msc Counteract Cancer Development and Growth?mentioning
confidence: 99%
“…An additional explanation is that within αSMA + myofibroblast are present subsets of cells with different functional behaviors, with either positive or negative effects on tumor cell growth. After depletion of all αSMA + myofibroblast, these populations are lost and PDAC can grow without any brake ( 168 , 173 , 175 , 177 , 183 ). In such TME, immune system can receive misleading information with conflicting, undesired outcomes.…”
Section: Can Msc Counteract Cancer Development and Growth?mentioning
confidence: 99%
“…Cancer cells can also remodel collagen fibers during the process of migration. 4,8 This can either act to change mechanical properties close to the cell 23 or locally disorganize or organize collagen fibers, thus amplifying 2,14 or dampening the original aligned collagen fiber signal. This results in different degrees of contact guidance and different invasion or metastasis rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of PSCs in ECM remodelling is gaining attention. Using an in vitro 3D spheroid tumour model and advanced imaging techniques, Drifka et al (115) demonstrated the permissive role of PSCs in fashioning the alignment of collagen fibres to facilitate the invasion and co-migration of cancer cells through the stroma. Similarly, Sada et al (116) also using a 3D culture setting, have reported that PSCs, in response to hypoxia, reorganised collagen fibres to a parallel alignment facilitating cancer cell migration.…”
Section: Interactions Of Pscs With Other Cells In the Stromamentioning
confidence: 99%